Hidden ileostomy as a rescue procedure in major colorectal surgeries: a novel technique to prevent re-laparotomy in anastomotic leak cases - Mohsen Ezzy; Moustafa Elshafei; Khalid Hamdi; Thomas Kraus; Peter Heinz; Michael Svoboda; Katrin Fleischer; Kersten Grimm; Stefan Berkhoff (Surgical Case Reports)
Abstract Background Anastomotic leak is a major cause of morbidity and mortality of patients worldwide, and it has remained stable over the last years. Routine construction of protective ileostomy is associated with stoma and negatively affects patients’ quality of life. Developing another technique to minimize those drawbacks with at least the same clinical success can help patients with anastomotic leak. We present the novel technique “Hidden Ileostomy” as an alternative to protective ileostomy that can achieve that balance. Materials and methods Eight patients presented to our department underwent the novel technique “Hidden Ileostomy” as a rescue procedure for different reasons. The associated risk factors and clinical scenarios, together with the follow-up data, are presented. Results For the eight cases in this study, one patient was ASA grade 1, 3 patients were classified as ASA grade 2, and 4 were grade 3. The mean ± SD operative time and blood loss were 196.3 ± 16.4 min and 325 ± 204.6 ml, respectively. The hidden ileostomy was removed after an average of 8 days. Only Case 6 reported an anastomotic leak on a postoperative day 10. Conclusion A hidden ileostomy is an alternative and feasible technique in selected cases in colorectal surgery. This technique could be adopted in our practice instead of routine instruction of ileostomy, especially in the equivocal anastomosis.